1979
DOI: 10.1111/j.1744-6570.1979.tb02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Verbal, Articulative, and Nonverbal Communication to Employment Decisions in the Job Interview Setting

Abstract: Recruiter ratings of 338 on‐campus interviews were used in a discriminant analysis procedure to determine the relative importance of the verbal, articulative, and nonverbal dimensions of communication during the job interview. Correlation of seven variables with the discriminant function indicated that appropriateness of content, fluency of speech, and composure were of greatest importance in contributing to a favorable employment decision. These findings were contrary to the recent literature which has emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 23 publications
3
77
1
Order By: Relevance
“…Furthermore, research has consistently shown that friendly nonverbal behaviors, especially eye contact, smiling, hand gesturing, and head nodding, are associated with higher interview evaluations (e.g., Anderson, 1991;Anderson & Shackleton, 1990;Burnett & Motowidlo, 1998;Cash & Kilcullen, 1985;DeGroot & Motowidlo, 1999;Forbes & Jackson, 1980;Gifford, Ng, & Wilkinson, 1985;Hollandsworth, Kazelskis, Stevens, & Dressel, 1979;Imada & Hakel, 1977;McGovern, Jones, Warwick, & Jackson, 1981;Motowidlo & Burnett, 1995;Parsons & Liden, 1984;Rasmussen, 1984). This leads to the following hypothesis, which basically attempts to replicate prior findings of a relationship between IM use (both verbal and nonverbal) and interview ratings.…”
Section: The Relationship Between Im Use and Im Effectivenesssupporting
confidence: 65%
“…Furthermore, research has consistently shown that friendly nonverbal behaviors, especially eye contact, smiling, hand gesturing, and head nodding, are associated with higher interview evaluations (e.g., Anderson, 1991;Anderson & Shackleton, 1990;Burnett & Motowidlo, 1998;Cash & Kilcullen, 1985;DeGroot & Motowidlo, 1999;Forbes & Jackson, 1980;Gifford, Ng, & Wilkinson, 1985;Hollandsworth, Kazelskis, Stevens, & Dressel, 1979;Imada & Hakel, 1977;McGovern, Jones, Warwick, & Jackson, 1981;Motowidlo & Burnett, 1995;Parsons & Liden, 1984;Rasmussen, 1984). This leads to the following hypothesis, which basically attempts to replicate prior findings of a relationship between IM use (both verbal and nonverbal) and interview ratings.…”
Section: The Relationship Between Im Use and Im Effectivenesssupporting
confidence: 65%
“…Moreover, the present study shows that the applicant's average turn duration and tempo variation predicts recruiter hiring decision. In other words, the applicant's average turn duration, an indicator of speech fluency (Fillmore 1979), can be seen as being validly extracted to the extent that it replicates previous research, which coded speech fluency manually (Hollandsworth et al 1979). In terms of the applicant's tempo variation, research has not yet investigated how it is related to hiring decision.…”
Section: Discussionmentioning
confidence: 72%
“…To decide which nonverbal behaviors to extract and focus on, we selected applicant nonverbal immediacy cues shown in previous research as being related to the hiring decision (e.g., Anderson and Shackleton 1990;Forbes and Jackson 1980;Hollandsworth et al 1979;Imada and Hakel 1977;McGovern and Tinsley 1978). For the visual nonverbal behavior we selected three cues being indicative of immediacy behavior: smiling, gazing, and visual back-channeling (i.e., nodding while listening to the interaction partner).…”
Section: Nonverbal Social Sensing In Actionmentioning
confidence: 99%
“…In some studies, communication skills were measured in a broad sense (i.e., rating the "communication skills" of the applicant; Dalessio & Silverhart, 1994;Landy, 1976), whereas other studies focused on specific aspects of communication. Exploring Methods for Developing BARS Dressel, 1979), as well as pitch, pausing, and speech rates (DeGroot & Kluemper, 2007;DeGroot & Motowidlo, 1999), has been shown to impact hireability judgments. The degree of power in speech (i.e., the extent to which participants are clear and direct) has also repeatedly been shown to be related to perceived employability and competence in interview settings (End & Saunders, 2013;Gibbons, Busch, & Bradac, 1991;Parton, Siltanen, Hosman, & Langenderfer, 2002).…”
Section: Communicationmentioning
confidence: 99%